A new discrete element model for simulating a flexible ring net barrier under rockfall impact comparing with large-scale physical model test data. (December 2019) - Zhu, Zhuo-Hui; Yin, Jian-Hua; Qin, Jie-Qiong; Tan, Dao-Yuan
Abstract: Flexible barriers are one of the effective mitigation measures to intercept high-energy falling rocks in mountainous areas, owing to its high ductility and excellent energy dissipation performance. This paper presents a newly developed flexible ring net barrier model based on the discrete element method (DEM) to simulate the rockfall impact on a flexible barrier. All the input mechanical parameters were calibrated by means of laboratory tests. The capabilities of the numerical model are evaluated by comparing the results from novel designed large-scale physical model impact tests. It is found that the new discrete element model is able to reproduce the behavior of a ring net barrier under rockfall impact. A good agreement with experimental data can be found regarding to boulder velocities, net elongations and tensile forces developed between ring net elements. In addition, the effects of boulder size, impact position, barrier inclination, and barrier initial slack on barrier response in a parametric study are investigated. The results from this study provide useful guidance for future design and optimization of rockfall barriers in engineering practice.